PENGUATAN KEMAMPUAN BENDAHARA DAN GURU SD MELALUI PEMBELAJARAN AKUNTANSI DASAR DI SDN MEKARWANGI, DS. MEKARWANGI, KEC. CISAUK, TANGERANG-BANTEN - Effendi, Bahtiar (UNIVERSITAS PGRI MADIUN, 2018)
Abstract. This activity aims to provide an adequate learning about the basic accounting of nonprofit entities to strengthen the ability of treasurers and teachers in recording and reporting of school financial books. The target of this activity is the teachers especially the school treasurer of SDN Mekarwangi.Problems resolved through two stages of learning and mentoring activities. The results of this activity show a positive impact with the improvement of teachers' skills related to school bookkeeping with the provision of the Principal's decision to appoint one teacher of the lesson participants to assistant treasurer. In addition, the results of other activities of the basic accounting concepts have been implemented in the private business of one of the teachers of the learning participants through the business of its sweet potato chips. Abstrak. Kegiatan ini bertujuan memberikan pembelajaran memadai mengenai akuntansi dasar entitas nirlaba guna penguatan kemampuan bendahara dan guru dalam pencatatan dan pelaporan pembukuan keuangan sekolah. Sasaran kegiatan ini adalah guru-guru terutama bendahara sekolah SDN Mekarwangi. Permasalahan diselesaikan melalui dua tahapan yakni kegiatan pembelajaran dan pendampingan. Hasil kegiatan ini menunjukkan dampak positif dengan peningkatan kemampuan guru terkait pembukuan sekolah dengan dibuktikannya keputusan Kepala Sekolah mengangkat satu guru peserta pembelajaranmenjadi asisten bendahara. Selain itu, hasil kegiatan lainnya konsep akuntansi dasar telah diimplementasi dalam usaha pribadi milik salah satu guru peserta pembelajaran melalui usaha keripik ubinya.